Computing three topological indices for Titania nanotubes TiO2[m, n]. Issue 3 (1st December 2016) - Liu, Jia-Bao; Gao, Wei; Siddiqui, Muhammad Kamran; Farahani, Muhammad Reza
Abstract: A numeric quantity which characterizes the whole structure of a graph is called a topological index. The concept of Generalized Zagreb, atom–bond connectivity ( A B C ) and geometric–arithmetic ( G A ) topological indices was established in chemical graph theory based on vertex degrees. Later on, other versions of A B C and G A indices were introduced and some of the versions of these indices are recently designed. In this article, we compute, Generalized Zagreb index G Z, fourth version of atom–bond connectivity ( A B C 4 ) index and fifth version of geometric–arithmetic ( G A 5 ) index for an infinite class of Titania nanotubes TiO 2 [ m, n ] .